The Influence of Motivation and Leadership Style on Employee Performance Through Work Environment as an Intervening Variable (Study at BTN KC Syariah Makassar) - Asniar, Asniar; Gani, Nuraeni; Mustamin, Asyraf (Study of Scientific and Behavioral Management, 2024)
In Indonesia, there are still many jobs related to the quality of human resources that need to be improved, which currently as many as 55% have low education and limited skills, as evidenced by the World Bank Human Capital Index 2023 report which places Indonesia at 130th out of 199 countries, as well as the EQ ranking which is ranked sixth in ASEAN. In this case, we will assess how far the influence of motivation and leadership style on employee performance through the work environment as a benchmark for assessing the job performance of each employee. This study uses a quantitative approach. The population in this study was 35 people. The data collection technique in this study used a questionnaire. The data obtained were then processed using SPSS 21. The results of this study indicate that Motivation, Leadership Style and work environment partially do not have a significant effect on employee performance. In addition, the results of the study also show that motivation and leadership style partially have a significant effect on the work environment. As for the results of the study, motivation and leadership style do not have a significant effect on performance with the work environment as an intervening variable